"Bitter Touch": Cross-modal associations between hand-feel touch and gustatory cues in the context of coffee consumption experience. (July 2020) - Pramudya, Ragita C.; Choudhury, Dipankar; Zou, Min; Seo, Han-Seok
Highlights: Hand-feel touch cues of cup-sleeve materials can be associated with specific taste qualities. Cross-modal associations of hand-feel touch exhibited with "imagined" and "consumed" tastes. Hand-feel touch cues of cup-sleeve materials affected consumer perception of brewed coffee. Physical attributes of sleeve materials could be related to cross-modal associations between hand-feel touch and taste cues. Abstract: Since a variety of packaging and containers have become commercially available in the market, there has been a rapidly growing interest in the influences of hand-feel touch cues on consumer perceptions and emotional responses toward food and beverage products. This study aimed to determine whether hand-feel touch cues of cup-sleeve materials could be associated with imagined (Study 1) and consumed (Study 2) basic tastes, and thereby affect the perception of brewed coffee (Study 3). Participants were asked to evaluate twelve different cup-sleeve materials with respect to evoked emotions and their degree of matching with each of the four basic taste qualities and brewed coffee-related flavor attributes (Study 1). Individual cup-sleeve materials were found to be more associated with specific taste qualities, coffee-related flavors, and emotions. Hand-feel touch cues of different sleeves were also found to be associated with taste qualities consumed (Study 2). For example, towel, linen, stainless steel, and cardboard materials were matched with sweet, salty, sour, and bitter taste qualities, respectively. Specific physical characteristics of cup-sleeve materials were found to be involved in mediating such cross-modal associations between hand-feel touch and taste cues. In Study 3, participants were asked to evaluate brewed coffee samples in paper cups both with cardboard sleeves and those made from the other test materials (towel, linen, and stainless steel). While participants rated black coffee samples with a towel sleeve less bitter than those with a cardboard sleeve, such differences were not observed in other pairwise comparisons. In conclusion, this study provided empirical evidence that hand-feel touch cues can be associated with specific taste or coffee-related flavor attributes, thereby modulating consumer perception of brewed coffee.